Compliant and Seamless Hybrid (Star and Mesh) Network Topology Coexistence for LoRaWAN: A Proof of Concept - Laura García; Carlos Cancimance; Rafael Asorey-Cacheda; Claudia-Liliana Zúñiga-Cañón; Antonio-Javier Garcia-Sanchez; Joan Garcia-Haro (Applied Sciences)
Long-range wireless area networks (LoRaWAN) typically use a simple star topology. However, some nodes may experience connectivity issues with the gateway due to signal degradation or limited coverage, often resulting from challenging environments in sectors such as agriculture, industry, smart cities, smart grids, and healthcare, where LoRaWAN-based IoT solutions have expanded. The main contribution of this paper is the implementation of a hybrid topology for LoRaWAN networks that remains fully transparent to current spec LoRaWAN servers and IoT applications. It enables the coexistence of mesh (multi-hop) and star (single-hop) communication schemes, dynamically adapting a node’s transmission mode based on physical link quality metrics. Additionally, the user interface allows for customizing network topology and parameters. Experimental proof-of-concept tests were conducted on a campus-wide testbed. Results showed that all devices successfully switched topology mode in 100% of the instances, enabling data transmission across all three scenarios under test. Network performance metrics were evaluated, with latencies ranging from 0.5 to 3.2 s for both single-hop and multi-hop transmissions. Additionally, improvements in RSSI and SNR were observed, validating the efficiency of the proposed solution. These results demonstrate the feasibility and effectiveness of our approach in extending network connectivity to areas beyond the gateway’s coverage.